2015
DOI: 10.1177/1203475415584867
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine Among Dermatology Outpatients

Abstract: There is a significant use of CAM among dermatology outpatients in Saudi Arabia. In view of the common belief that CAM has fewer side effects than conventional medicine, dermatologists need to increase their awareness of CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…All the studies collected data from some region or study in Saudi Arabia, however only a single study reported information for Saudi Arabia without specifying any study. 20 These studies are not comparable to the present view since they identified the use of herbal medicine across Saudi Arabia relative to a particular disease or disorder such as, dermatology.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…All the studies collected data from some region or study in Saudi Arabia, however only a single study reported information for Saudi Arabia without specifying any study. 20 These studies are not comparable to the present view since they identified the use of herbal medicine across Saudi Arabia relative to a particular disease or disorder such as, dermatology.…”
Section: Resultscontrasting
confidence: 62%
“…21 Eight of the studies identified explicitly used the term 'herbal medicine' to represent the research 13,14,18,[23][24][25][26] while 11 of them used the term complementary and alternative medicine. 15,16,20,27,28,29,30,31 Differences in the results of these studies can be attributed to the differences in study objectives, methodology, population characteristics, sample size, and study design. These differences made it difficult to precisely define the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary and alternative medicine, extensively used for the treatment of disease ( 9 ), may be an alternative approach in decreasing the side effects of patients with cancer undergoing chemotherapy, which compromises patients quality of life ( 10 ). Natural compounds are well recognized for the management of several diseases, including CML ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned reasons, most studies focused on CAM utilization among adults or pediatric populations with no particular focus on CAM use in older adults. In Saudi Arabia, many studies looked at CAM use among samples where Saudi older adults (SOA) were only a subgroup of study samples rather than being the main focus of the study [18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For instance, Al-Faris and colleagues conducted a cross-sectional study that examined CAM use in 1408 Saudi adults in the Riyadh region.…”
Section: Introductionmentioning
confidence: 99%